Invisible Labour in the Woodwardian Collection - Joshua Hillman (Museum & Society)
As is widely known, the ‘Woodwardian Collection’ at the Sedgwick Museum, Cambridge, holds the nearly 10,000 rock, mineral, and fossil specimens collected by the eccentric English natural historian John Woodward between 1688 and 1728. Less widely appreciated, however, is the extent to which Woodward’s collection depended on the ‘invisible labour’ of mineworkers, gem cutters, and other labourers. In this article, I use some of Woodward’s extant field notes to reconstruct his debts to these labourers. As I argue, the taxonomic schemes for metallic ores and gems that Woodward proposed in a scientific treatise of 1728 owed more to the intellectual, as well as physical, labour of the mineworkers and gem cutters that he encountered in the field than is suggested in the treatise itself. The Woodwardian Collection is thus an ideal case study for rendering the invisible labour behind mineral collections more visible.